2011
DOI: 10.1016/j.cell.2011.08.053
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Circuits and Synaptic Mechanisms Underlying Motor Initiation in C. elegans

Abstract: Summary C. elegans is widely used to dissect how neural circuits and genes generate behavior. During locomotion, worms initiate backward movement to change locomotion direction spontaneously or in response to sensory cues; however, the underlying neural circuits are not well defined. We applied a multidisciplinary approach to map neural circuits in freely-behaving worms by integrating functional imaging, optogenetic interrogation, genetic manipulation, laser ablation, and electrophysiology. We found that a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
356
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(393 citation statements)
references
References 47 publications
35
356
2
Order By: Relevance
“…The AVA interneurons are important to initiate backward movements (23)(24)(25)(26). We found that expression of the dbl-1 coding region using the nmr-1 promoter, whose expression overlaps with dbl-1 expression only in AVA, significantly rescued the learning defect in dbl-1(nk3) mutant animals ( Fig.…”
Section: Dbl-1 Produced By the Ava Command Interneurons Promotes Avermentioning
confidence: 67%
See 1 more Smart Citation
“…The AVA interneurons are important to initiate backward movements (23)(24)(25)(26). We found that expression of the dbl-1 coding region using the nmr-1 promoter, whose expression overlaps with dbl-1 expression only in AVA, significantly rescued the learning defect in dbl-1(nk3) mutant animals ( Fig.…”
Section: Dbl-1 Produced By the Ava Command Interneurons Promotes Avermentioning
confidence: 67%
“…S5 A and B). Because calcium influx of AVA is correlated with the initiation of spontaneous backward movements (26,35,36), we recorded AVA calcium dynamics of animals in the nematode growth medium (NGM) buffer using a microfluidic device that allows generation of body waves, which result in forward or backward movements (36). We measured the G-CaMP fluorescence intensity in AVA in naive and PA14-trained animals and calculated the rate of intensity change (Fig.…”
Section: Dbl-1 Signals To the Hypodermis To Direct Aversive Olfactorymentioning
confidence: 99%
“…The nematode Caenorhabditis elegans is particularly ideal for optical neurophysiology owing to its small size, optical transparency, compact nervous system, and ease of genetic manipulation. Imaging systems for tracking the activity of small numbers of neurons have been effective in determining their role during nematode locomotion and navigational behaviors like chemotaxis, thermotaxis, and the escape response (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…In C. elegans, nociceptive sensations and avoidance have been intensively studied. However, the reported studies were focused on the functional mapping of the connections among sensory neurons and interneurons, using cell ablation, optogenetic manipulation and in vivo calcium imaging [4][5][6][7] . Therefore, the peripheral modulation of nociceptive sensations and avoidance behaviours is poorly understood.…”
mentioning
confidence: 99%